THE EFFECT OF WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT WATER RESOURCES DEPARTMENT, COPYRIGHT WORKS AND SPATIAL PLAN OF NORTH SUMATRA PROVINCE - Herlina - Dalimunthe (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2022)
This study entitled